The effects of aqueous leaf extract of Portulaca oleracea on haemato-biochemical and histopathological changes induced by sub-chronic aluminium toxicity in male wistar rats - Derouiche Samir; Chetehouna Sara; Atoussi Widad (Elsevier, 2022)
Background: Purslane has wide acceptability as a potherb in Central Europe, Asia, and Mediterranean region, it is very used in traditional Chinese medicine (TCM) to treat fever, dysentery, diarrhea, carbuncles, eczema, and to remove toxic substances. Our study aimed to investigate the impact of purslan on physiological and biochemical alterations induced by AlCl3 intoxication in rats. Methodology: Fifteen males albino Wistar rats were randomly divided into 3 groups (n = 5); healthy rats (Control), AlCl3 (200 mg/kg b.w) treated rats and AlCl3 (200 mg/kg b.w) rats treated with aqueous extract of P. oleracea (400 mg/kg b.w). AlCl3 treatments were given to rats orally for 70 days and purslan extract for 21 days. Various parameters as hematological, biochemical, oxidative stress markers and liver histopathology were estimated. In-vitro study of plant, some quantitative parameters was analyzed using standard protocols. Results: In vitro phytochemical test results revealed that purslane contains most of the principal active molecules, especially flavonoids and phenolic compounds. In vivo results, the AlCl3 group showed an alteration in the antioxidant defend system by increasing the MDA level and decreasing the GSH levels, GST and SOD activities compared to control. Furthermore, the hematological parameters revealed that AlCl3 induce an inflammation in rats by significant raise (P<0.01) of WBC, Monocyte, LYM and platelet (P<0.001) levels with a significant perturbation in lipid profile and biochemical parameters. In the other hand, histopathological analysis recorded a deep modification in liver tissues of AlCl3 rats group compared to control. However, the treatment of AlCl3 rats by purslan ensured a partial amelioration and correction of the previous parameters. Conclusion: We conclude that the use of purslane seems to be the powerful limited of AlCl3 toxicity development, which opening the new horizons for the use of phytotherapy in medical approach.